Testicular Sparing Surgery For A 5-Year- Old Boy with Sertoli's Cell Tumour of the Testis: Case Report (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Introduction: Steroli's cell tumors SCT are the rare testicular tumor. Very few cases were published in the literature. A new case of Sertoli's cell tumor that is reported and treated by testicular sparing surgery.Case Presentation: A 5-year-old boy with Sertoli' cell tumor presents with gynaecomastia and precocious puberty. He was treated by successful testicular sparing surgery.Conclusions: SCTs are rare testicular tumors. Testicular sparing surgery can be applied.